In the Quiet Season and Other Stories - Amore, Martha (Book collections on Project MUSE., 2018)
"In the Quiet Season and Other Stories explores the human landscape of Alaska. While the stories take place in modern day towns, each is laced with a timelessness that comes from their roots in ageless issues: broken trust and heartbreak, hope and rebirth. The expansive Alaska landscape infuses the stories with a unique chill, as tears freeze on eyelashes and mountain ranges form the backdrop for breakups. Although the people in Amore's stories know how to survive Alaska's cold terrain, these characters stumble when trying to navigate through their own lives and lost dreams" -- From the publisher.